Three-year pot culture of Epipactis helleborine reveals autotrophic survival, without mycorrhizal networks, in a mixotrophic species - May, Michał; Jąkalski, Marcin; Novotná, Alžběta; Dietel, Jennifer; Ayasse, Manfred; Lallemand, Félix; Figura, Tomáš; Minasiewicz, Julita; Selosse, Marc-André (Mycorrhiza, 2020)
Some mixotrophic plants from temperate forests use the mycorrhizal fungi colonizing their roots as a carbon source to supplement their photosynthesis. These fungi are also mycorrhizal on surrounding trees, from which they transfer carbon to mixotrophic plants. These plants are thus reputed difficult to transplant, even when their protection requires it. Here, we take profit of a successful ex situ pot cultivation over 1 to 3 years of the mixotrophic orchid Epipacis helleborine to investigate its mycorrhizal and nutrition status. Firstly, compared with surrounding autotrophic plants, it did not display the higher N content and higher isotopic (13C and 15N) abundance that normally feature mixotrophic orchids because they incorporate N-, 13C-, and 15N-rich fungal biomass. Second, fungal barcoding by next-generation sequencing revealed that the proportion of ectomycorrhizal fungi (expressed as percentage of the total number of either reads or operational taxonomic units) was unusually low compared with E. helleborine growing in situ: instead, we found a high percentage of rhizoctonias, the usual mycorrhizal partners of autotrophic orchids. Altogether, this supports autotrophic survival. Added to the recently published evidence that plastid genomes of mixotrophic orchids have intact photosynthetic genes, this suggests that at least some of them have abilities for autotrophy. This adds to the ecological plasticity of mixotrophic plants, and may allow some reversion to autotrophy in their evolution.
Keywords: Rhizoctonia; Stable isotopes; autotrofní procesy; 13C; 15N; Mycoheterotrophy; mykorhiza; Plant Roots; Orchid transplantation; Symbiosis; symbióza; Autotrophic Processes; kořeny rostlin; Orchidaceae; fotosyntéza; Photosynthesis; Mycorrhizae